Long Noncoding RNA SNHG4 Attenuates the Injury of Myocardial Infarction via Regulating miR-148b-3p/DUSP1 Axis. (5th December 2022) - Wang, Sheng; Cheng, Zhaoyun; Chen, Xianjie; Lu, Guoqing; Zhu, Xiliang; Xu, Gaojun
Abstract : Objective . Long noncoding RNAs (lncRNAs), including some members of small nucleolar RNA host gene (SNHG), are important regulators in myocardial injury, while the role of SNHG4 in myocardial infarction (MI) is rarely known. This study is aimed at exploring the regulatory role and mechanisms of SNHG4 on MI. Methods . Cellular and rat models of MI were established. The expression of relating genes was measured by qRT-PCR and/or western blot. In vitro, cell viability was detected by MTT assay, and cell apoptosis was assessed by caspase-3 level, Bax/Bcl-2 expression, and/or flow cytometry. The inflammation was evaluated by TNF- α, IL-1 β, and IL-6 levels. The myocardial injury in MI rats was evaluated by echocardiography, TTC/HE/MASSON/TUNEL staining, and immunohistochemistry (Ki67). DLR assay was performed to confirm the target relationships. Results . SNHG4 was downregulated in hypoxia-induced H9c2 cells and MI rats, and its overexpression enhanced cell viability and inhibited cell apoptosis and inflammation both in vitro and in vivo . SNHG4 overexpression also decreased infarct and fibrosis areas, relieved pathological changes, and improved heart function in MI rats. In addition, miR-148b-3p was an action target of SNHG4, and its silencing exhibited consistent results with SNHG4 overexpression in vitro . DUSP1 was a target of miR-148b-3p, which inhibited the apoptosis of hypoxia-induced H9c2 cells. Both miR-148b-3p overexpression and DUSP1 silencing weakened the effects of SNHG4 overexpression on protecting H9c2 cells against hypoxia. Conclusions . Overexpression of SNHG4 relieved MI through regulating miR-148b-3p/DUSP1, providing potential therapeutic targets.